PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN JSEVEN COFFEE PEKANBARU - Zul Iqbal Kurniawan; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Jseven Coffee Pekanbaru uses marketing communication techniques by way of Word of Mouth, where this communication technique is considered the most appropriate and effective to be used as promotional media. The reason is because word of mouth communication is considered more convincing based on information on a product because the source is satisfied with the quality of the product and also this technique is considered to be easier and right on target than other types of promotion. Satisfied consumers will of course disseminate this information to other consumers, so that this benefits JSeven Coffee Pekanbaru and also for potential customers. The purpose of this study was to find out how much influence Word Of Mouth has on the purchasing decisions of Jseven Coffee Pekanbaru customers. The theory used in this study is the Stimulus Response theory. The research method used in this study is a quantitative research method, with data collection techniques, namely, distributing questionnaires directly to visitors of Jseven Coffee Pekanbaru with a sample size of 100 respondents determined through the Accidental Sampling technique. The data analysis technique in this study used a simple linear regression analysis technique. The results of this study indicate that the value of the regression coefficient in this study is Y = 2.108 + 279 (X). The constant number (a) is 2.108 and the coefficient of the variable X is 1.112. Meanwhile tcount (9.188) is greater than ttable (1.984). Based on the statistical calculations obtained, the hypothesis for this study is that Ha has a significant influence between the influence of Word Of Mouth (X) on the purchasing decision of Jseven Coffe Pekanbaru visitors (Y). So that means Ha is accepted and H0 is rejected. Based on the correlation interpretation guidelines, a correlation coefficient (r) of 0.291 is obtained, it means that the relationship between the Word Of Mouth variable and the purchasing decision of Jseven Coffee Pekanbaru visitors is in the weak category. Furthermore, the value of the coefficient of determination (Rsquare) is 0.85. This means that it can be explained that the purchasing decisions of Jseven Coffee Pekanbaru customers are influenced by word of mouth while the rest are influenced by other variables not examined in this study.